Three new species of Mesobiotus (Eutardigrada: Macrobiotidae) from Sweden with an updated phylogeny of the genus - Sarah Atherton; Jens Hulterström; Roberto Guidetti; K. Ingemar Jönsson (Scientific Reports)
Abstract Three new species of Mesobiotus (Tardigrada: Eutardigrada: Macrobiotidae) are described from Skåne County in the southernmost region of Sweden. All three species are distinguished morphologically and through differences in DNA sequences as supported by PTP and mPTP analyses. With the addition of Mesobiotus bockebodicus sp. nov., M. skanensis sp. nov., and M. zelmae sp. nov., the number of nominal species of Macrobiotidae in Sweden has increased to 26, 73% of which have been documented from Skåne. Finally, new morphological details and DNA sequences are presented for Mesobiotus emiliae, a new record is presented of M. mandalori from Sweden, and the phylogenetic relationships within the genus is reconstructed using previously published and new 18S and COI gene sequences.